ECONOMIC DIVERSIFICATION AS A TOOL FOR POVERTY REDUCTION - Fozilov Vahobjon Akrom o’g’li (TADQIQOTLAR, 2026)
Annotation.  This  article  examines  the  role  of  economic  diversification  in reducing poverty and ensuring sustainable economic development. The study analyzes how diversification of economic sectors contributes to employment growth, income stability, investment expansion, and social welfare improvement. Particular attention is  paid  to  industrial  diversification,  service  sector  development,  digital  economy, innovation,  and  export  diversification.  The  article  also  evaluates  statistical relationships between diversified economic structures and poverty reduction indicators in developing countries.